Gisbertus Voetius (1589-1676) on the Freedom of the Will : An Elucidation of Andreas J. Beckâ€™s â€œThe Will as Master of Its Own Actâ€ - Thamrindinata, Hendra (JURNAL TEOLOGI REFORMED INDONESIA, 2020)
Kausalitas Ilahi dan kebebasan manusia adalah topik yang hangat diperdebatkan pada awal masa modern antara kaum Reformed dan Yesuit, Sosinian, dan Remonstran, khususnya setelah kon-troversi antara kaum Yesuit dan Dominikan dalam Congregatio de Auxiliis. Para lawan menuduh pandangan Reformed mengajarkan fatalisme Stoik. Esai ini akan mengulas pandangan tentang kebebasan kehendak dari Gisbertus Voetius, seorang teolog Reformed pada periode High Ortho-doxy, sebagaimana diulas oleh Andreas J. Beck dalam â€œThe Will as Master of Its Own Act: A Disputation Rediscovered of Gisbertus Voetius (1589-1676).â€ Ulasan ini didasarkan atas karya Voetius yang terlupakan: Disputatio philosophico-theologico, continens quaestiones duas, de Dictinctione Attributorum divinorum, & Libertate Voluntatis, yang dibela oleh Engelbertus Beckman dalam sebu-ah disputasi di bawah arahan Voetius pada tahun 1652. Esai ini akan menunjukkan bahwa ke-bebasan manusia bagi Voetius adalah prinsip formal bagi aksinya sendiri, dan bahwa kebebasan tersebut kompatibel dengan keniscayaan hipotetis yang berasal dari dekrit Ilahi, premosi fisik, serta dengan ultimate practical judgement akal budi. Keniscayaan kebebasan manusia yang ber-fungsi di dalam keniscayaan ini adalah sebuah keniscayaan yang penuh. The divine causality and humanâ€™s freedom were hotly debated topics during the early modern era between Reformed and Jesuits, Socinians, and the Remonstrants, particularly at the aftermath of the controversy between Jesuits and Dominicans in Congregatio de Auxiliis. Reformedâ€™s view was accused as teaching Stoic fatalism by its opponents. This paper will elucidate the view of Gisbertus Voetius, a Reformed theologian in the period of High Orthodoxy, on the freedom of the will, as exposed by Andreas J. Beck in his article, â€œThe Will as Master of Its Own Act: A Disputation Rediscovered of Gisbertus Voetius (1589-1676)â€ which was based on Voetiusâ€™s forgotten Disputatio philosophico-theologico, continens quaestiones duas, de Dictinctione Attributorum divinorum, & Libertate Voluntatis, defended by Engelbertus Beckman in 1652 and presided by Voetius himself. It will show that for Voetius, human freedom was a formal principle of its own act and was compatible with hypothetical necessities originated from divine decree, physical premotion, and ultimate practical judgement of the intellect. Functioning within these necessities, human freedom was not more necessitated by them than by itself.